Poverty and Distributional Analysis of Electricity Poverty and Protection of Vulnerable Customers in Kosovo - World Bank (World Bank, Washington, DC, 2021)
The objective of the report is to inform the preparation of a Government Program for establishing the status of customers in need, the scope of their rights, and protection measures to help them meet demands for electricity in case of electricity tariff increases. The report analyzes patterns of electricity consumption, affordability, poverty and distributional impacts of hypothetical scenarios of tariff increases. It also reviews the current protection mechanism with an electricity subsidy, models the impact of short- and medium-term reform options, and recommends concrete mitigation measures. In accordance with Law No. 05/L-085 on Electricity of 2016, the Government of Kosovo should develop a detailed Program for establishing the status of customers in need, the scope of their rights, and protection measures to help them meet demands for electricity. Electricity accounts for almost 90 percent of the total energy expenditures of households in Kosovo, and over 97 percent of the energy expenditures of poor households.1 According to the Law on Electricity2, the Ministry of Labor and Social Welfare (MLSW) in cooperation with the Ministry of Energy, Ministry of Finance and in consultation with the Energy Regulatory Office (ERO) and other stakeholders of the electricity sector should develop a social protection program (Program), providing social benefits to ensure the necessary electricity supply to customers in need, or providing for support for energy efficiency improvements, to address energy poverty. Such measures shall not impede the effective opening of the electricity market and its functioning. Customers in need are household consumers, who, due to social status, enjoy some special rights regarding the supply with electricity, to be provided in exceptional cases. Commitment to the development of this Program is taken also with Kosovo’s Energy Strategy, and with the requirements of the Treaty of Energy Community as defined by the Third Energy Package3. The Program should propose an approach to identifying the electricity poor who are vulnerable and outline short- and medium-term measures for their protection.